de Sitter JT gravity from double-scaled SYK - Kazumi Okuyama (Journal of High Energy Physics)
Abstract It is known that the double-scaled SYK model (DSSYK) reduces to JT gravity with a negative cosmological constant by zooming in on the lower edge E = – E 0 of the spectrum. We find that the de Sitter JT gravity (i.e. JT gravity with a positive cosmological constant) is reproduced from DSSYK by taking a scaling limit around the upper edge E = E 0 of the spectrum. We also argue that the appearance of de Sitter JT gravity is consistent with the behavior of the classical solution of the sine dilaton gravity.